A criação como ferramenta pedagógica no ensino do piano: dando voz ao professor-compositor - Eduardo Dias de Barros Filho (2019)
The creative practices – composition, improvisation and arrangements elaboration – integrate the new paradigms of piano’s pedagogy. With the relevance of the discussions about these new paradigms, the specificities and variety in the profile of contemporary students as background, this research sought to investigate and discuss the importance of the figure of teacher-composer in the current scenario of piano teaching. For this, three different methodological approaches were used. In the first moment, a literature review was made about the teacher's formation, his professional performance and the new paradigms of piano pedagogy. Then, interviews were conducted with three important teacher-composers of the present time: Laura Longo (Brazil), Hudson Neves Carvalho (Brazil) and June Armstrong (Ireland). In the last stage, which is configured as a self-ethnographic artistic research, an authorial artistic product was presented, followed by the narrative of the process of composition and application of the pieces, as well as the interweaving of the voices of three teacher-composers with the voice and the experience music-didactic of the researcher. The analysis of the interviews revealed that the three teacher-composers are not reproducing their training, and that the use of creative practices in their professional practice emerged from the demands raised by different contexts and the variety of the contemporary student profile, which requires greater versatility of the music educator. The Keith Swanwick's C(L)A(S)P Model was presented as an ideal model not only for the integral formation of the student, but also as a model for the formation and performance of the contemporary piano teacher.